The effectiveness of the use of Robinson’s Strategy SQ3R in developing reading absorption skills with my timeless language course for middle-class second-graders - Harthi, Yasmeen Mohammad (Journal of Educational and Psychological Sciences, 2020)
The aim of the research was to reveal the effectiveness of the use of the Robinson Strategy (SQ3R) in the development of reading absorption among middle-class second-grade students in the course of my timeless language course in Mecca. There are statistically significant differences at the level of significance (α≤0.05) between the average scoring of reading absorption skills (literal, inference, and monetary) in application (tribal-dimensional) in favor of the experimental group, and between the effect of the Robinson Strategy (SQ3R) in the development of reading absorption among middle-school students, the researcher recommended several recommendations, the most important of which is the use of the Robinson Strategy (SQ3R) in the teaching of Arabic language for the purposes of achieving effective learning.